Linguistic Representation of Gender Stereotypes in Spanish - Andriychenko, Yuliia; Popova, Nataliia; Chorna, Nataliia; Bratel, Olena (Jurnal Arbitrer, 2024)
The purpose of this study was to analyse gendered speech standards and patterns in Spanish, considering lexical and grammatical features. The following methods were used in the study: deductive, content analysis, and structural. Furthermore, the lexical materials of researchers who have addressed the issue of gender stereotypes in speech were considered. The results of the study showed that in Spanish, gender stereotypes can transmit and reinforce inequalities between men and women through the use of certain words, phrases, word combinations, and constructions. This is due to the way language is used and understood in society. Linguistic gender stereotypes in Spanish develop in the grammatical, lexical, and semantic fields, considering speech customs that can both strengthen and weaken the role of the individual. The content analysis revealed that gender-neutral templates are beginning to be actively used in the modern Spanish environment, leading to the inclusiveness of the language. With the global development of attitudes towards gender roles, speech stereotypes are changing, most notably in statements, addresses and forms of politeness. However, to effectively overcome linguistic inequality in speech, it is necessary to comprehensively implement the ideology of inclusiveness and gender culture in the fields of education, society, and government, using practical mechanisms that consider race, class, culture, and the role of each person in society.